PLATELET DERIVATIVES WITH DENTAL MEDICINE APPLICATIONS - Hurjui Ion; Delianu Carmen; Hurjui Loredana Liliana; Jipu Raluca; Mitrea Mihaela; Balcoș Carina; Armencia Adina Oana; Mârțu Maria Alexandra; Grădinaru Irina (Romanian Society of Oral Rehabilitation, 2020)
he role of platelets is to trigger the inflammatory response which, in turn, will trigger the presence of tissue growth factors that will be involved in the tissue repair process. Platelet rich plasma (PRP) is a concentrate used for therapeutic purposes which has become increasingly used by treating various dermatological pathologies, musculoskeletal disorders and not least with increasingly frequent indications in the pathology of the oro-dento-maxillare sphere, as a consequence of its potential to repair tissues with reduced regeneration capacity and apparent harmlessness. PRP is defined as a plasma preparation with a higher platelet content than found in the blood flow of a healthy individual (200 000 per microliter) typically 5 times higher. This study in the literature aims to review the biological basis of PRP, its preparation and processing for its use as well as its main applications. At the same time, another derivative of practical importance in dental medicine, PRF (plateled rich fibrin), is presented. PRF is a second-generation PRP thrombocyte concentrate, which provides the implant dentist with access to growth factors through a simple and up-to-date technology. These growth factors are autologous, non-toxic and non-immunogenic, increasing and accelerating normal bone regeneration pathways.